Fertility, agricultural labor supply, and production: Instrumental variable evidence from Uganda - Van Campenhout, Bjorn (International Food Policy Research Institute, 2014)
Human fertility is likely to affect agricultural production through its effect on the supply of agricultural labor. Using the fact that in traditional, patriarchal societies sons are often preferred to daughters, we isolated exogenous variation in the number of children born to a mother and related it to agricultural labor supply and production outcomes in Uganda—a country that combines a dominant agricultural sector with one of the highest fertility rates in the world. We found that fertility has a sizable negative effect on household labor allocation to subsistence agriculture. Households with lower fertility devote significantly more time to land preparation and weeding, while larger households grow less matooke and sweet potatoes. We found no significant effect on agricultural productivity as measured in terms of yield per land area.